Melancholia versus tradycja. Jarosław Marek Rymkiewicz - Świeściak, Alina (Wydawnictwo Naukowe UAM w Poznaniu, 2010)
In this article various manifestations of melancholy syndrome in Jarosław Marek Rymkiewicz’s poetry created after 1989 are analysed. However, his previous works are also studied. The problem of the relation of melancholy to tradition and the past in its classical understanding is researched as it is of key importance for understanding the oeuvre of the author of Animula. Referring to Harold Bloom’s theory, the author shows the melancholy relation of Rymkiewicz’s poetry with tradition, first of all in reference to the poetry of Baroque and to Bolesław Leśmian. Rymkiewicz’s melancholy also consists of the attitude to death which is present in this poetry and the transgressive treatment of corporality as well as understanding of the language as the one which from the very beginning is marked by the lack, traumatised and suspending communication.